(untitled) (Педагогіка вищої та середньої школи, 2012)
Статтю присвячено проблемі емоційного інтелекту в контексті формування професійної культури студентів-менеджерів у вищому навчальному закладі. Наведено вимоги до менеджера ХХІ ст. Представлено вихідні передумови для формування емоційного інтелекту та очікувані внаслідок пропонованих дій результати. Ключові слова: навчання у ВНЗ, професійна культура, емоційний інтелект. The article deals with the problem of emotional intelligence in the context of the formation of a professional culture of the students in the university managers. Are the requirements to the manager of the twenty-first century. Shows the initial premise for the formation of emotional intelligence and the expected results due to the proposed action. Key words: teaching at the university, professional culture, emotional intelligence.